Wind-Vehicle-Bridge Coupling Simulation Analysis of Flexible Hanger Arch Bridge in Suspended Monorail Transit - ZENG Min (Chengshi guidao jiaotong yanjiu)
［Objective］ Due to the characteristics of small structural stiffness and small width-span ratio of the track beam, the flexible hanger arch bridge in suspended monorail transit is vulnerable to wind loads, thus influencing the safety of the bridge structure and the ride comfort of trains. Therefore, it is necessary to conduct research on the wind-vehicle-bridge coupling structure. ［Method］ With the first suspended monorail transit line in China as the engineering background, a flexible 80-meter hanger arch bridge model is established by the ANSYS finite element software. The wind-vehicle-bridge coupling analysis is carried out through the Fluent finite element software and the multi-body dynamics software UM, and the running condition of the vehicle is judged by the ride comfort index. ［Result & Conclusion］ Under the action of wind loads, the lateral ride comfort index of the train changes more drastically than the vertical one, and the ride comfort is on the verge to the train operation requirements. When the train speed and wind speed increase, the lateral vibration of the train will be significantly enhanced. At the train speed of 40 km/h, compared with the wind speed of 10 m/s, the maximum lateral displacement of the bridge increases by 159.5% with a wind speed of 20 m/s, and the maximum vertical displacement increases by 11%. While the maximum lateral displacement of the bridge increases by 70% with a wind speed of 15 m/s, the maximum vertical displacement increases by 24.1%.